Doktrin pluralisme agama: telaah konsep dan implikasinya bagi agama-agama - Thoha, Anis Malik (Sekolah Tinggi Agama Islam Negeri (STAIN) Ponorogo, Insonesia, 2011)
The pro's-and-con's of Religious Pluralism continues to exist, and it seems that this will not come to an end in the near future. Within this discourse, there has persistently been something very disturbing, i.e., that the very concept of Religious Pluralism has never been touched or understood in a way it was defined technically and philosophically by the experts. As such, this paper is an attempt to argue that as the term Religious Pluralism is a foreign term adopted unconsciously by the Muslims, it thus needs desperately to be evaluated critically in terms of its doctrines and implications that eventually will pose a threat to all religions.